2013
DOI: 10.4103/2249-4847.123092
|View full text |Cite
|
Sign up to set email alerts
|

Study of umbilical cord blood culture in diagnosis of early-onset sepsis among newborns with high-risk factors

Abstract: Context:Blood culture is gold standard for diagnosis of neonatal sepsis. Low sensitivity of blood culture is usually due to small volume of blood sample, intrapartum antibiotics, and antibiotics given to newborn before sampling.Aim:We evaluated use of Umbilical cord blood culture (UCBC) in diagnosis of neonatal sepsis as compared to peripheral venous blood culture.Settings and Design:This study was done in tertiary care teaching hospital during May-June 2012. A total of 45 newborns with presence of two or more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…This study also showed that pathogens were more implicated in peripheral blood than the umbilical cord swab samples. A contrary report was documented by other researchers where the authors discovered that a total of 24.4% high risk newborns had positive lab culture when umbilical cord blood sample was used (11 out of 45) and 8 out of 45 newborn had positive peripheral blood sample culture [ 32 ]. Differences in specimen samples could explain this disparity; whereas the present study also used umbilical cord swab as specimen, Kalathia et al [ 32 ] used only umbilical cord blood as specimen.…”
Section: Discussionmentioning
confidence: 89%
“…This study also showed that pathogens were more implicated in peripheral blood than the umbilical cord swab samples. A contrary report was documented by other researchers where the authors discovered that a total of 24.4% high risk newborns had positive lab culture when umbilical cord blood sample was used (11 out of 45) and 8 out of 45 newborn had positive peripheral blood sample culture [ 32 ]. Differences in specimen samples could explain this disparity; whereas the present study also used umbilical cord swab as specimen, Kalathia et al [ 32 ] used only umbilical cord blood as specimen.…”
Section: Discussionmentioning
confidence: 89%
“…7 Although blood culture is gold standard for diagnosis of neonatal sepsis, the use of intra-partum antibiotics and empirical antibiotics prior to collecting blood for culture decreases yield of culture. 2,[8][9][10] For choosing the appropriate empirical therapy, one should be aware of the common organisms causing EOS and LOS, so that the antibiotic resistance and emergence of MDR organisms can be reduced. The present study aims to find the common organisms causing neonatal sepsis and their antibiotic sensitivity pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Cord blood culture has comparable organism detection to peripheral venous blood culture. 19 The sensitivity of cord blood culture is 80-100% and specificity is 91-94%, while the positive and negative predictive value are 33-72% and 94-100%, respectively. 19,20 It is less invasive and painful, easier to preform, and a larger volume of blood is available compared with peripheal blood cultures.…”
Section: Discussionmentioning
confidence: 96%